SARS-CoV-2 spike proteins react with Au and Si, are electrically conductive and denature at 3 × 108 V m−1: a surface bonding and a single-protein circuit study - Dief, E.M.; Darwish, Nadim (2023)
Developing means to characterise SARS-CoV-2 and its new variants is critical for future outbreaks. SARS-CoV-2 spike proteins have peripheral disulfide bonds (S-S), which are common in all spike proteins of SARS-CoV-2 variants, in other types of coronaviruses (e.g., SARS-CoV and MERS-CoV) and are likely to be present in future coronaviruses. Here, we demonstrate that S-S bonds in the spike S1 protein of SARS-CoV-2 react with gold (Au) and silicon (Si) electrodes. Bonding to Si is induced by a spontaneous electrochemical reaction that involves oxidation of Si-H and the reduction of the S-S bonds. The reaction of the spike protein with Au enabled single-molecule protein circuits, by connecting the spike S1 protein between two Au nano-electrodes using the scanning tunnelling microscopy-break junction (STM-BJ) technique. The conductance of a single spike S1 protein was surprisingly high and ranged between two states of 3 × 10−4G0 and 4 × 10−6G0 (1G0 = 77.5 μS). The two conductance states are governed by the S-S bonds reaction with Au which controls the orientation of the protein in the circuit, and via which different electron pathways are created. The 3 × 10−4G0 level is attributed to a single SARS-CoV-2 protein connecting to the two STM Au nano-electrodes from the receptor binding domain (RBD) subunit and the S1/S2 cleavage site. A lower 4 × 10−6G0 conductance is attributed to the spike protein connecting to the STM electrodes from the RBD subunit and the N-terminal domain (NTD). These conductance signals are only observed at electric fields equal to or lower than 7.5 × 107 V m−1. At an electric field of 1.5 × 108 V m−1, the original conductance magnitude decreases accompanied by a lower junction yield, suggesting a change in the structure of the spike protein in the electrified junction. Above an electric field of 3 × 108 V m−1, the conducting channels are blocked and this is attributed to the spike protein denaturing in the nano-gap. These findings open new venues for developing coronavirus-capturing materials and offer an electrical method for analysing, detecting and potentially electrically deactivating coronaviruses and their future variants.